Indeks Pemerataan Guru (IPG): Ikhtiar Mempercepat Distribusi Guru - Kholid Novianto (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2020)
One of the big problems experienced by the world of education today is the unequal distribution of teachers. In an area there is often a shortage and an excess of teachers at once. This problem should not have occurred if the local government was able to implement policies on teacher equalization optimally. In order to accelerate the distribution of teachers, the Director General of GTK, Ministry of Education and Culture will issue a Teacher Equity Index (IPG) as a measuring tool to determine the extent to which inequality in teacher distribution occurs in all regions in Indonesia. Through IPG, it will be easy to monitor the extent to which teacher distribution policies have been implemented. If the GPA of a region is getting lower, it is a sign that the region has implemented an equalization policy for teachers. However, if the IPG score is constant, this indicates that the region has not implemented an optimal teacher distribution policy. With the existence of IPG, it is hoped that each region will be motivated to accelerate the policy of equalization of teachers so that the data on teacher needs will be known in a more real way.